Models for the formation of it company strategic portfolio of projects - Lysytskyi, V. L.; Orlenko, D. Yu. (НТУ "ХПИ", 2018)
Increasing of unpredictability, novelty and complexity of the external environment of modern enterprises of IT industry has led to the need of creating such management mechanisms that can ensure making of coordinated and effective decisions to adapt enterprises to the external competitive environment, ensure their survival and successful development. In order to adapt to rapidly changing environmental conditions it is necessary to apply management that is associated not so much with the definition of a strategic position (long-term and strategic planning), as with a timely, real-time response to rapid and unexpected changes. Formation of adequate management forces enterprises to engage in the refinement of the strategy and the solution of the arisen strategic tasks simultaneously and in parallel, to apply scientifically based management information technologies. Сreation of such technologies requires the availability of adequate models of production activities of IT company. A set of interrelated models of forming a strategic portfolio of IT projects of a company, whose activity is aimed at creating a finite number of IT projects in the context of time and resource constraints, is proposed. A set of interrelated models for the formation of IT projects strategic portfolio activity of which is aimed at creating a finite number of unique software products in conditions of time and resource constraints is proposed. Qualitative and quantitative methods of modeling of IT company production activity were used while developing a set of models and generated a set of models of expert procedure and a set of models of optimization procedure. The set of expert procedure models for assessing of IT projects significance realizes the hierarchies analysis method. The set of models of optimization procedure implements the method of linear programming which allows to determine the effective structure of the IT projects portfolio in the medium term which ensures achievement of company strategic goals. Based on the developed set of models, a generalized algorithmic model for the formation of company strategic portfolio of projects is formed and can be used to create information technology for strategic planning of IT company production activities in conditions of dynamic external environment.

Повышение непредсказуемости, новизны и сложности внешнего окружения современных предприятий ИТ индустрии привели к необходимости создания таких механизмов управления, которые способны обеспечить принятие скоординированных и эффективных решений по адаптации предприятий к внешней конкурентной среде и обеспечению их выживания и успешного развития. Для адаптации к быстро меня- ющимся условиям среды требуется применение управления, связанного не столько с определением стратегической позиции (долгосрочное и стратегическое планирование), сколько со своевременной реакцией в реальном масштабе времени на быстрые и неожиданные изменения. Формирование адекватного управления вынуждает предприятия одновременно параллельно заниматься уточнением стратегии и решением возникших стратегических задач, применять научно обоснованные информационные технологии управления. Создание таких технологий требует наличия адекватных моделей производственной деятельности ИТ фирмы. Предлагается комплекс взаимосвязанных моделей формирования стратегического портфеля проектов ИТ фирмы, деятельность которой направлена на создание конечного числа ИТ проектов в условиях временных и ресурсных ограничений. При создании комплекса моделей использованы качественные и количественные методы моделирования производственной деятельности ИТ предприятия, породившие комплекс моделей экспертной процедуры и комплекс моделей оптимизационной процедуры. Экспертная процедура обеспечивает оценку значимости ИТ проектов с использованием метода анализа иерархий. Комплекс моделей оптимизационной процедуры реализует метод линейного программирования, позволяющий в среднесрочной перспективе определить эффективную структуру стратегического портфеля ИТ проектов, обеспечивающего достижение стратегических целей ИТ фирмы. На основе построенного комплекса моделей разработана обобщенная алгоритмическая модель формирования стратегического портфеля ИТ проектов, которая может быть использована при создании информационной технологии стратегического планирования производственной деятельности ИТ предприятия в условиях динамической внешней среды
Модели формирования стратегического портфеля проектов IТ фирмы
Keywords: set of models; optimization procedure; expert procedure, portfolio; expert procedure; portfolio of IT projects; комплекс моделей; оптимизационная процедура; экспертная процедура; портфель IT проектов; информационная технология